Presacral venous bleeding during mobilization in rectal cancer - Casal Núñez, Jose Enrique (World J Gastroenterol, 2017)
AIM: To analyze the anatomy of sacral venous plexus flow, the causes of injuries and the methods for controlling presacral hemorrhage during surgery for rectal cancer. METHODS: A review of the databases MEDLINE(®) and Embase™ was conducted, and relevant scientific articles published between January 1960 and June 2016 were examined. The anatomy of the sacrum and its venous plexus, as well as the factors that influence bleeding, the causes of this complication, and its surgical management were defined. RESULTS: This is a review of 58 published articles on presacral venous plexus injury during the mobilization of the rectum and on techniques used to treat presacral venous bleeding. Due to the lack of cases published in the literature, there is no consensus on which is the best technique to use if there is presacral bleeding during mobilization in surgery for rectal cancer. This review may provide a tool to help surgeons make decisions regarding how to resolve this serious complication. CONCLUSION: A series of alternative treatments are described; however, a conventional systematic review in which optimal treatment is identified could not be performed because few cases were analyzed in most publications.